Dupilumab modulates specific IgE mite responses at the molecular level in severe T2-high atopic dermatitis: A real-world experience - González-Pérez, Ruperto; Poza-Guedes, Paloma; Mederos-Luis, Elena; Sánchez-Machín, Inmaculada (Frontiers in Medicine, 2022)
Background Atopic dermatitis (AD) is regarded as a chronic systemic disease which is characterized by a robust overexpression of type 2 related cytokines, with increased total IgE levels and a concomitant sensitization to common allergens. Dupilumab, a fully human monoclonal antibody (mAb) to IL-4Rα that inhibits both IL-4 and IL-13 signaling, has previously shown a marked and rapid improvement when treating the moderate-to-severe forms of AD. We sought to evaluate the real-world evidence (RWE) of dupilumab in the modulation of total and specific IgE (sIgE) serum levels to a panel of molecular house dust mites (HDM) and storage mites (SM) allergens in patients with severe AD. Methods Demographic and clinical data for severe AD adult patients receiving dupilumab treatment (300 mg every 2 weeks) were reviewed. Mean (standard deviations SD) values and percent changes from baseline in total and sIgE to the complete HDM and SM extracts, and 14 individual molecular allergens were measured over 52 weeks. Results Significant (p < 0.05) changes in mean total IgE levels were observed from baseline to week-52 after treatment with dupilumab. Despite no changes were found in sIgE against the extract of HDM during the 52-week treatment with dupilumab, baseline mean levels from 7 out of 14 individual molecular mite allergens -Der p 1, Der p 2, Der p 5, Der p 7, Der p 21, Der p 23, and Lep d 2- were significantly (p < 0.05) decreased—after 52 weeks of treatment with dupilumab. Conclusions Dupilumab therapy for 52 weeks resulted in a profound reduction in blood levels of total IgE and allergen-specific IgE to both HDM and SM at the molecular level in adults with severe AD under RWE conditions. The potential benefits of these concomitant immunomodulatory effects after treatment with dupilumab should be explored to a greater extent.